Elevated peripheral leukocyte counts in acute cervical artery dissection. Issue 10 (12th June 2013) - Grond‐Ginsbach, C.; Giossi, A.; Aksay, S. S.; Engelter, S. T.; Lyrer, P. A.; Metso, T. M.; Metso, A. J.; Tatlisumak, T.; Debette, S.; Leys, D.; Thijs, V.; Bersano, A.; et al.
Abstract : Background and purpose: It has been suggested that inflammation may play a role in the development of cervical artery dissection (CeAD), but evidence remains scarce. Methods: A total of 172 patients were included with acute (< 24 h) CeAD and 348 patients with acute ischaemic stroke (IS) of other (non‐CeAD) causes from the Cervical Artery Dissection and Ischemic Stroke Patients (CADISP) study, and 223 age‐ and sex‐matched healthy control subjects. White blood cell (WBC) counts collected at admission were compared across the three groups. Results: Compared with healthy control subjects, CeAD patients and non‐CeAD stroke patients had higher WBC counts ( P  <   0.001). Patients with CeAD had higher WBC counts and were more likely to have WBC > 10 000/μl than non‐CeAD stroke patients (38.4% vs. 23.0%, P  <   0.001) and healthy controls (38.4% vs. 8.5%, P  <   0.001). WBC counts were higher in CeAD (9.4 ± 3.3) than in IS of other causes (large artery atherosclerosis, 8.7 ± 2.3; cardioembolism, 8.2 ± 2.8; small vessel disease, 8.4 ± 2.4; undetermined cause, 8.8 ± 3.1; P  =   0.022). After adjustment for age, sex, stroke severity and vascular risk factors in a multiple regression model, elevated WBC count remained associated with CeAD, as compared with non‐CeAD stroke patients [odds ratio (OR) = 2.56; 95% CI 1.60–4.11; P  <   0.001) and healthy controls (OR = 6.27; 95% CI 3.39–11.61; P  <   0.001). Conclusions: Acute CeAD was associated with particularly high WBC counts. Leukocytosis may reflect a pre‐existing inflammatory state, supporting the link between inflammation and CeAD.